1993
DOI: 10.1055/s-2006-959601
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Biological Effects of 7-O-Methyleriodictyol, a Flavanone Isolated fromArtemisia monosperma, on Rat Isolated Smooth Muscles

Abstract: The isolation for the first time from the genus Artemisia (Compositae) of the known flavanone, 7-O-methyleriodictyol (7-methoxy-5,3',4'-trihydroxy-flavanone), its identification, and its biological effects on rat isolated smooth muscles are described. 7-O-Methyleriodictyol (10(-7) M to 3 x 10(-4) M) caused concentration-dependent inhibition of the amplitude of the phasic contractions and reduced the tone of the ileum, the uterus, and the urinary bladder. It also caused relaxation of the phenylephrine-precontra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 7 publications
(9 reference statements)
2
12
0
1
Order By: Relevance
“…These results may cause irritation and stretch of uterine cervix (neurogenic reflex), which may stimulate the posterior pituitary gland to increase its secretion of OT (Guyton, 2006). In another area of in vitro studies, it was reported that Artemisia monosperma extract, exerted a relaxant effect of uterine smooth muscle and inhibited the contraction of the uterus that induced by oxytocin (Abu-Niaaj et al, 1993).…”
Section: Effect Of Leaves Ethanolic Extract On Parturitionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may cause irritation and stretch of uterine cervix (neurogenic reflex), which may stimulate the posterior pituitary gland to increase its secretion of OT (Guyton, 2006). In another area of in vitro studies, it was reported that Artemisia monosperma extract, exerted a relaxant effect of uterine smooth muscle and inhibited the contraction of the uterus that induced by oxytocin (Abu-Niaaj et al, 1993).…”
Section: Effect Of Leaves Ethanolic Extract On Parturitionmentioning
confidence: 99%
“…Artemisia monosperma reported to contain several phytochemicals such as volatile oil (Saleh, 1985), flavonoids (Ismail et al, 1989;Abu-Niaaj et al, 1993;Elgamal et al, 1997), alkaloids (Zaki et al, 1984) and coumarins (Hammoda et al, 2008). Coumarins are known to inhibit mail fertility (Ray et al, 1991) and to inhibit under the number: A9864 at the Herbarium of Jordan University.…”
Section: Introductionmentioning
confidence: 99%
“…insecticidal, 9 anti-malarial 10 and anticancer activities. 11 Various types of secondary metabolites were reported in A. monosperma plants from different localities including: coumarins, 12,13 flavonoids, [14][15][16] acetylenes, 9,17,18 alkaloids, 19 sesquiterpenoids 20 and triterpenoids. 16 However, nothing could be traced in the available literature concerning either the constituents or biological activities of the plant growing in Libya.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are bioactive compounds with a wide spectrum of biological activities including their effects on smooth muscles. 8,15,16,29,30 Artemisia monosperma is a good source of flavonoids and is reputed in folk medicine in the Middle East for the relief of abdominal illness, inflammation and for inducing labor. Several flavonoids isolated from A. monosperma were reported to induce relaxation of different rat smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
“…1 Different extracts of A. monosperma exhibited a wide spectrum of biological actions such as muscle relaxation, [6][7][8] antidiabetic, 1,8 and antimicrobial activities. [9][10][11][12][13][14] Bioactive compounds isolated from Artemisia species showed antispasmodic, 15,16 antihypertensive, 17 antimicrobial, 12,13 insect repellents, [18][19][20] antitumor and anti-inflammatory activities. [21][22][23] Arcapillin was first identified from A. capillaris 24 and it was reported an antihepatotoxic.…”
Section: Introductionmentioning
confidence: 99%